"We are sliding into uncharted territory, and we are alone in this.” A New Look At Political Disorientation - Tonello, Fabrizio (Review of International American Studies, 2018)
For million of citizens, the experience of voting is now similar to the one of advancing through uncharted territory. The article looks at the origins of this feeling, tracing the history of political disorientation in the US and comparing it to the one of other industrial democracies.